This kind of war the classic Korean war history - Fehrenbach, T. R. (1998)
"The authoritative, highly acclaimed classic history of the Korean War, This Kind of War is a dramatic and hard-hitting account of the conflict written from the perspective of those who fought it. Partly drawn from official records, operations journals, and histories, it is based largely on the compelling personal narratives of the small-unit commanders and their troops."--Jacket.